Improvement Strategy of Employee Performance PT. Perkebunan Nusantara V - Hendrasyah Putra; Syamsul Maarif (Media Ekonomi dan Manajemen, 2019)
PT. Perkebunan Nusantara V is one of the companies engaged in oil palm plantations. During the 2011-2017 period PTPN V carried out the recruitment and selection process with a span of 2 years. New employees from the results of recruitment, selection and placement are required to always improve performance. The purpose of this study is to determine the effect of recruitment on performance, the effect of selection on performance, the effect of placement on performance, the effect of recruitment on selection, and the influence of selection on placement, as well as strategies to improve employee performance in PTPN V. This study uses Structural Equation Model Partial Least Squares (PLS-PLS) and the Analytic Hierarchy Process (AHP) to test the hypothesis. The sample of this study is 90 employees. The results of this study show that recruitment has no effect on performance, selection has a significant effect on employee performance, placement has a significant effect on employee performance, recruitment has a significant effect on selection and selection has a significant effect on placement. Then the results of the formulation of the right strategy is to improve employee welfare, development of performance and competency based HRM, improve the recruitment system according to needs and improve performance monitoring and evaluation.